Professor, intérprete e aluno surdo: uma relação além da comunicação nas aulas de Educação Física - Ayoub, Ronan Ahmad Juste (2020)
This research aims to investigate, discuss and analyze how a physical education teacher acts in theoretical and practical classes with deaf students, with and without an interpreter presence, based on the Theory of Communicative Action, by Habermas (2012). We start from the principle that the traditional expository classes restrict the relations of the deaf student with the interpreter and it causes a deficient interaction with the school staff including with the teacher himself/herself. Although, in this educational context, it is essential the interpreter presence to the development of the deaf student, considering that this professional mediates among the participants by oral communication and the deaf student affectivity with this professional promotes positive effects to the student´s development. We used as methodological instruments the reflexive diary, elaborated along the professional career of the researcher who followed the student for two years, and semi-structured interviews with the actors of the studied phenomenon: the interpreter, the deaf student, the pedagogical coordinator and another physical education teacher who taught in the Elementary school with the same student. We concluded that during the Physical Education practices, considering the use of motricity, the deaf student as well as the other staff school members look for communicative tools to solve the problems, in order to not be so dependent of the interpreter, with direct communication among the subjects. We also conclude that in traditional expository classes, the deaf student limits to the interpreter, and by doing it restricts his/her communication and relation with the present teacher as well as the staff school members. A proposed suggestion was the productive groupings as a methodological possibility based on communicative rationality.